Mechanism of anti‐inflammatory effects of rifampicin in an ex vivo culture system of hidradenitis suppurativa. Issue 7 (28th January 2022) - Haferland, Isabel; Wallenwein, Chantal M.; Ickelsheimer, Tanja; Diehl, Sandra; Wacker, Matthias G.; Schiffmann, Susanne; Buerger, Claudia; Kaufmann, Roland; Koenig, Anke; Pinter, Andreas
Abstract: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease of the hair follicles leading to painful lesions, associated with increased levels of pro‐inflammatory cytokines. Numerous guidelines recommend antibiotics like clindamycin and rifampicin in combination, as first‐line systemic therapy in moderate‐to‐severe forms of inflammation. HS has been proposed to be mainly an auto‐inflammatory disease associated with but not initially provoked by bacteria. Therefore, it has to be assumed that the pro‐inflammatory milieu previously observed in HS skin is not solely dampened by the bacteriostatic inhibition of DNA‐dependent RNA polymerase. To further clarify the mechanism of anti‐inflammatory effects of rifampicin, ex vivo explants of lesional HS from 8 HS patients were treated with rifampicin, and its effect on cytokine production, immune cells as well as the expression of Toll‐like receptor 2 (TLR2) were investigated. Analysis of cell culture medium of rifampicin‐treated HS explants revealed an anti‐inflammatory effect of rifampicin that significantly inhibiting interleukin (IL)‐1β, IL‐6, IL‐8, IL‐10 and tumour necrosis factor (TNF)‐α production. Immunohistochemistry of the rifampicin‐treated explants suggested a tendency for it to reduce the expression of TLR2 while not affecting the number of immune cells.